The Effect Of Work Family Conflict And Work Life Balance On The Performance Of Employees In The Palm Oil Production Division At PT. Wanasari Riau Province Archipelago - Bhayangkara, Rama Bintang; Basriani, Agustin; Joesyiana, Kiki (STEBIS Bina Mandiri, 2025)
Work-life balance is a crucial issue in contemporary work environments. This study aims to analyze the influence of work-family conflict and work-life balance on employee performance at PT Wanasari Nusantara Company, Riau Province. Survey research method was used to collect data from 61 respondents who are production employees of PT Wanasari Nusantara Company, Riau Province. Multiple linear regression analysis was used to test the research hypothesis. These findings indicate the importance of human resource management in paying attention to these aspects to improve employee performance. The practical implications of this study are the need for policies and programs that support employee work-life balance, as well as strategies to manage work-family conflict to improve individual and organizational performance.